BOOK REVIEW: "Rosa Lee: A Mother and Her Family in Urban America" - Smith-McKeever, T. Chedgzsey (Reflections: Narratives of Professional Helping, 2014)
BOOK REVIEW. Leon Dash. Rosa Lee: A Mother and Her Family in Urban America. New York: Basic Books, 1996, 279pages. 23.00 hardcover, ISBN 0-465-07092-2. No abstract.